THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Venalia Vivi Setiawati; Sofia Ulfa Eka Hadiyanti; Yulia Tri Kusumawati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study was conducted to examine the influence of the work environment and work motivation on employee performance at the Department of Communication and Informatics of East Kalimantan Province. Both variables are considered important elements in supporting the improvement of effectiveness, productivity, and the quality of task implementation within a government organization. This research employed a quantitative approach involving 94 employees as respondents. The collected data were analyzed using multiple linear regression to determine the partial and simultaneous effects of each independent variable on employee performance. The results indicate that the work environment and work motivation have a significant effect on employee performance, both individually and collectively. A conducive work environment creates comfort in carrying out tasks, while high work motivation enhances discipline, responsibility, and productivity. However, the ability of these two variables to explain variations in performance remains limited, suggesting that other potential factors should also be considered. Keywords: Work Environment; Work Environment; Employee Performance